The use of handheld marker to calibrate a field-programmable gate array based eye tracker for artificial vision system - Caspi, Avi; Roy, Arup; Barry, Michael P.; Sadeghi, Roksana; Kartha, Arathy; Dagnelie, Gislin (Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Annual International Conference, 2020)
Tracking the eye of a blind patient can enhance the usability of an artificial vision system. In systems where the sensing element, i.e. the scene camera that captures the visual information, is mounted on the patient's head, the user must use head scanning in order to steer the line of sight of the implant to the region of interest. Integrating an eye tracker in the prosthesis will enable scanning using eye movements. The eye position will set the region of interest within the wide field-of-view of the scene camera. An essential requirement of an eye tracker is the need to calibrate it. Obviously, off-the-shelf calibration methods that require looking at known points in space cannot be used with blind users.Here we tested the feasibility of calibrating the eye-tracker based on pupil position and the location of the percept reported by the implant recipient, using a handheld marker. Pupil positions were extracted using custom image processing in a field-programmable-gate-array built into a glasses-mounted eye tracker. In the calibration process, electrodes were directly stimulated and the subject reported the location of the percept using a handheld marker. Linear regression was used to extract the transfer function from pupil position to gaze direction in the coordinates of the scene camera.In using the eye tracker with the proposed calibration method, patients demonstrated improved precision on a localization task with corresponding reduction of head movements.